Cellulose in Foliage and Changes during Seasonal Leaf Development of Broadleaf and Conifer Species - Zoltan Kern; Adam Kimak; István Gábor Hatvani; Daniela Maria Llanos Campana; Markus Leuenberger (Plants, 2022)
Stable isotope approaches are widely applied in plant science and many improvements made in the field focus on the analysis of specific components of plant tissues. Although technical developments have been very beneficial, sample collection and preparation are still very time and labor-consuming. The main objective of this study was to create a qualitative dataset of alpha-cellulose content of leaf tissues of arboreal species. We extracted alpha-cellulose from twelve species: Abies alba Mill., Acer pseudoplatanus L., Fagus sylvatica L., Larix decidua Mill., Picea abies (L.) Karst., Pinus sylvestris L., Quercus cerris L., Quercus petrea (Matt.) Liebl., Quercus pubescens Wild., Quercus robur L., Tilia platyphyllos Scop. and Ulmus glabra Huds. While these species show an increase in cellulose yield from bud break to full leaf development, the rates of increase in cellulose content and the duration of the juvenile phase vary greatly. Moreover, the veins display significantly higher alpha-cellulose content (4 to 11%) compared to blade tissues, which reflects their different structural and biochemical functions. A guide for the mass of sample material required to yield sufficient alpha-cellulose for a standard stable isotope analysis is presented. The additional benefits of the assessment of the mass of required sample material are reduced sample preparation time and its usefulness in preparing samples of limited availability (e.g., herbarium material, fossil samples).